3D Heads-Up Display vs. Standard Operating Microscope Vitrectomy for Rhegmatogenous Retinal Detachment - Asani, Ben; Siedlecki, Jakob; Schworm, Benedikt; Mayer, Wolfgang J.; Kreutzer, Thomas C.; Luft, Nikolaus; Priglinger, Siegfried G. (Frontiers in Medicine, 2020)
Purpose: To assess the efficacy and outcomes of 23-gauge vitreoretinal surgery for rhegmatogenous retinal detachment using a three-dimensional heads-up display (3D HUD) surgical platform as compared to a standard operating microscope (SOM) setting. Design: Retrospective cohort study Participants: One hundred and forty consecutive eyes of 140 patients with primary retinal detachment Methods: All eyes underwent 23-gauge pars plana vitrectomy for primary retinal detachment using either a 3D HUD (NGENUITY; Alcon Inc., Fort Worth, Texas, USA; n=70 eyes) or a SOM setting (n=70 eyes); in cases of significant cataract, additional phacoemulsification with intraocular lens (IOL) implantation was performed. Minimum follow-up was two months. Main outcome measures: Primary retinal reattachment rate, rate of proliferative vitreoretinopathy (PVR), best-corrected visual acuity (BCVA), duration of surgery Results: There were 70 eyes each in the 3D HUD and the SOM group. Both groups did not differ concerning age (p=0.70), extent of retinal detachment (p=0.07), number of retinal tears (p=0.40), macular involvement (p=0.99) and preoperative BCVA (p=0.99). Postoperatively, 3D HUD and SOM were comparable concerning the primary retinal reattachment rate (88.6 vs. 94.3 %; p=0.37), the development of postoperative PVR (12.9 % vs. 7.1 %; p=0.40) and final BCVA (0.26±0.40 vs. 0.21±0.38 logMAR; p=0.99). Duration of surgery was significantly longer in the 3D HUD group (66.2±16.5 vs. 61.2±17.1 min; p=0.04), an effect which however vanished after a “learning curve” of the first 35 eyes (p=0.49). Conclusions: On par results to a conventional operating microscope can be achieved with a 3D HUD setting when performing 23-gauge vitreoretinal surgery for rhegmatogenous retinal detachment, including the primary retinal reattachment rate, the incidence of postoperative PVR and final BCVA. However, duration of surgery might initially be slightly longer with 3D HUD, suggesting the effect of a learning curve.